2016
DOI: 10.1055/s-0041-110136
|View full text |Cite
|
Sign up to set email alerts
|

Renal Pseudoaneurysms and Arteriovenous Fistulas as a Complication of Nephron-Sparing Partial Nephrectomy: Technical and Functional Outcomes of Patients Treated With Selective Microcoil Embolization During a Ten-Year Period

Abstract: Purpose: The aim of this study was to evaluate the clinical and functional outcomes in patients who underwent selective interventional embolization of renal pseudoaneurysms or arteriovenous fistulas at our center. Materials and Methods: Our retrospective analysis included all consecutive patients who received selective transcatheter embolization of renal pseudoaneurysms or arteriovenous fistulas after partial nephrectomy in our department from January, 2003 to September, 2013. The technical and clinical succe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 13 publications
(23 reference statements)
3
24
1
Order By: Relevance
“…[ 6 ] Clinical success was defined as absence of clinical and imaging evidence of bleeding as determined by the resolution of gross hematuria, retroperitoneal bleeding, further decrease in hemoglobin and hypotension, after TAE. [ 7 ] Postembolization syndrome (PES) was defined as fever, abdominal pain, nausea, or vomiting after TAE. [ 8 ]…”
Section: Methodsmentioning
confidence: 99%
“…[ 6 ] Clinical success was defined as absence of clinical and imaging evidence of bleeding as determined by the resolution of gross hematuria, retroperitoneal bleeding, further decrease in hemoglobin and hypotension, after TAE. [ 7 ] Postembolization syndrome (PES) was defined as fever, abdominal pain, nausea, or vomiting after TAE. [ 8 ]…”
Section: Methodsmentioning
confidence: 99%
“…A large, multi-center retrospective study of 998 minimally invasive partial nephrectomy procedures found that approximately 2% resulted in iatrogenic vascular injury ( 15 ). A study of 1,425 patients in Germany undergoing partial nephrectomy found similar results, with 2.7% resulting in pseudoaneurysm or arteriovenous fistula ( 16 ). Pseudoaneurysms, though rare, usually present around 14.9 days after surgery ( 17 ).…”
Section: Ae In Renal Traumamentioning
confidence: 79%
“…The reported incidence ranges between 1.00–2.7%,2, 3 occurring more frequently in laparoscopic compared to open partial nephrectomies 2, 4. The three most common presentations of RAP are gross hematuria, flank pain, and anemia, 2 with most patients presenting usually around two weeks postop 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The three most common presentations of RAP are gross hematuria, flank pain, and anemia, 2 with most patients presenting usually around two weeks postop 2 . Untreated, RAPs can lead to severe hematuria, blood loss, hemorrhagic shock, and even death 3, 4…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation